Ferroptosis and Its Potential Role in Human Diseases - Han, Chu; Liu, Yuanyuan; Dai, Rongji; Ismail, Nafissa; Su, Weijun; Li, Bo (Frontiers in Pharmacology, 2020)
Ferroptosis is a novel regulated cell death pattern discovered when studying the mechanism of erastin killing RAS mutant tumor cells in 2012. It is an iron-dependent programmed cell death pathway mainly caused by increased redox imbalance but with distinct biological and morphology characteristic compared to other known cell death patterns. Ferroptosis is associated with various diseases including acute kidney injury, cancer, and cardiovascular, neurodegenerative, and hepatic diseases. Moreover, activation or inhibition of ferroptosis using a variety of ferroptosis initiators and inhibitors can modulate disease progression in animal models. In this review, we provide a comprehensive analysis of the characteristics of ferroptosis, its initiators and inhibitors, and the potential role of its main metabolic pathways in the treatment and prevention of various diseased states. We end the review with the current knowledge gaps in this area to provide direction for future research on ferroptosis.